Multi-Mode adhesives performance and success/retention rates in NCCLs restorations: randomised clinical trial one-year report. Issue 1 (20th December 2019) - Manarte-Monteiro, Patrícia; Domingues, Joana; Teixeira, Liliana; Gavinha, Sandra; Manso, Maria Conceição
Abstract: Aim: Compare clinical performance and success/retention rates of two multi-mode (MM) adhesives, applied in self-etch (SE) or etch-and-rinse (ER) modes, with SE-all-in-one adhesive (SE/SE with enamel etching) in NCCL restorations at one-year follow-up. Material and methods: Prospective, double-blind RCT approved by the University Fernando Pessoa and the National-Clinical-Research-Ethics Committees (CEIC-20150305), ClinicalTrials.gov registered (NCT02698371), in 38 participants with 210 restorations (AdmiraFusion ® ) randomly allocated to six groups (Adhesives_Adhesion mode), each with 35 restorations: G1-Control Futurabond ® DC_SE; G2-Control Futurabond ® DC_SE with enamel etching; G3-Futurabond ® U_ER; G4-Futurabond ® U_SE; G5-Adhese ® Universal_ER; G6-Adhese ® Universal_SE. Restorations evaluated at baseline and one-year by three calibrated examiners (ICC ≥0.952) using FDI criteria and statistical analysis with nonparametric tests (alpha = 0.05). Results: At one-year recall 36 participants, 199 restorations were available for examination; five (2.5%) restorations (G1 n  = 2; G2, G3, G4 n  = 1) were lost due to retention ( p  > .05); G1 showed less satisfying marginal adaptation ( p  < .05) than G2 and MM adhesives groups, particularly G6. Overall success rates ( p  > .05) were: 93.9% (G1), 97.0% (G2; G3; G4) and 100.0% (G5; G6). Conclusions: MM adhesives (Futurabond ® U and Adhese ® Universal) showed similar and acceptable performance/success rates but also better clinical outputs than the SE-all-in-one adhesive (Futurabond ® DC), particularly in SE mode. Success and retention rates were similar and not dependent on materials or adhesion modes.